2021
DOI: 10.1371/journal.pone.0248815
|View full text |Cite
|
Sign up to set email alerts
|

Environmental awareness and guests’ intention to visit green hotels: The mediation role of consumption values

Abstract: The paper aimed at examining the influence of consumer’s environmental awareness on their intention to visit green hotels in north Cyprus, the mediation role of consumption values. Research on eco-friendly hotels stressed that conventional hotels do not make available to consumers the environmental awareness and consumption values, whereas, there is possibility that these benefits might not sit well with the hotel potential consumers. Aside highlighting the features of green hotels, it is imperative to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 89 publications
(163 reference statements)
2
21
1
Order By: Relevance
“…But surprisingly, it plays an insignificant role in influencing the green hotel decision in Bangladesh. The finding contradicts the early studies that if customers believe that their green approach would produce positive outcomes, they would be more likely to be engaged in that given behavior which may lead to make them pick a green hotel choice (Ajzen, 1991; Demir et al. , 2021; Jiang and Kim, 2015).…”
Section: Discussion and Implications Of The Studycontrasting
confidence: 60%
“…But surprisingly, it plays an insignificant role in influencing the green hotel decision in Bangladesh. The finding contradicts the early studies that if customers believe that their green approach would produce positive outcomes, they would be more likely to be engaged in that given behavior which may lead to make them pick a green hotel choice (Ajzen, 1991; Demir et al. , 2021; Jiang and Kim, 2015).…”
Section: Discussion and Implications Of The Studycontrasting
confidence: 60%
“…Meanwhile, anthropocentric attitudes did not influence as mediator on the link of environmental knowledge, altruism and intention toward visiting green hotels. Some studies found no mediating effect of attitude while connecting behavioural intention in the hotel industry (Demir et al, 2021;Sadiq et al, 2022). The reason could be that having environmental knowledge and altruistic behaviour might lead to a negative perception of green development and infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is proposed that the mediation role of ecocentric and anthropocentric attitudes is important in determining green purchasing decisions (Perrea et al, 2014). In addition to those tourists concerned with the environment and its sustainability, they are likely to have a positive attitude towards the environment, which will lead to green purchasing intention (Demir et al, 2021;Prakash et al, 2019). Understanding how consumers' ecocentric and anthropocentric attitudes mediate the relationships that lead to green hotel intention is critical.…”
Section: Mediating Role Of Ecocentric and Anthropocentric Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years the customers themselves are becoming increasingly aware of sustainability issues, including environmental, social, and economic implications; and sustainable consumer behaviour and mindset has been extensively reviewed in various academic researches as well as has gathered significant attention in the hospitality consumer marketplace (Heesup, 2021;Tasci, 2017;Verma, Chandra, 2018;Demir at al., 2021). Same sources are deliberating the severe economic decline and required immediate response, encompassing the social, environmental, and economic impact of the operations, not just as an accountability tool but to drive strategy from it, unlocking new sources of revenue and sustainable growth.…”
Section: Introductionmentioning
confidence: 99%